PENINGKATAN KEMAMPUAN MENULIS TEKS PROSEDUR DENGAN MODEL PJBL BERBASIS AI PADA SISWA KELAS XI TBSM 2 SMKN 4 PALEMBANG - Nia, Nia Rahma Sari; Missriani, Missriani; Wahyu Indrawati, Sri (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2025)
This study aims to improve students' skills in writing procedural texts using the Project-Based Learning (PjBL) model assisted by Artificial Intelligence (AI) for XI TBSM 2 students at SMK Negeri 4 Palembang for the 2024/2025 academic year. This research is a type of classroom action research. The method used is classroom action research. The research subjects consisted of 35 students of XI TBSM 2. The instruments used in this study include (1) action planning, (2) action implementation, (3) observation, and (4) reflection. Based on the results and discussion of the research, it is concluded that students' skills in writing procedural texts using the Project-Based Learning model through AI in XI TBSM 2 class at SMK Negeri 4 Palembang have improved. In cycle I, 24 students achieved mastery with a total score of 2755, an average of 78.57 or (68.57%). In cycle II, mastery increased with a total score of 2953, an average of 84.37 or (94.29%). The results of this study are expected to increase active participation and creativity of students in generating ideas in the ability to write procedural texts.